Frequency of Depression in Patients Presenting with Migraine at Tertiary Care Hospital Quetta - Naseeb Ullah; Khan, Hazrat Ali; Khan, Zain Ullah; Abdul Khalid, Sahibzada; Anwar, Mohammad; Abdul Qadir; Amin Ullah; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Headache is one of the commonest complaints of patients of all ages and both   genders. General headaches have a lifetime prevalence of more than 95% to 97% and it is common knowledge that almost every individual experiences a    headache in his life, which is mostly benign and subsides with self-medication. International classification of    headache disorders in its 2nd edition has discussed a large number of Primary Headaches including migraine. Objective: The objective of the current study was to evaluate the frequency of depression in patients presenting with migraine at the tertiary care hospital Quetta. Methods:  Cross sectional study Non-probability convenience-based sampling technique was used to calculate the sample size of N=119 patients. The sample population    included all patients between 18-60 years of age and either gender (i.e. male or female) having a history of migraine headache of two months’ duration. Study was conducted Baluchistan Institute of Psychiatry and Behavioral Sciences) BIPBS Quetta. Duration of the Study: Duration of Study:  From 15th July 2022 to 15th January 2023. Result: This study involved 119 migraine patients, with a mean age of 27.59±5.37 years, a median duration of six months, and three migraine attacks. Most were males, married, or unmarried. The highest proportion was graduates, followed by intermediate-level individuals. Conclusion: The results report a high prevalence of depression amongst patients with Migraines. These migraine attacks are also    reported to be associated with nausea and changes in vision.